Optimization by Response Surface Methodology of Biodiesel Production from Podocarpus falcatus Oil as a Cameroonian Novel Nonedible Feedstock - Serges Bruno Lemoupi Ngomade; Raoul Donald Tchuifon Tchuifon; Rufis Fregue Tiegam Tagne; Meme Laloi Tongnang Ngueteu; Hugues Mahouli Patai; George Ndifor-Angwafor Nche; Solomon Gabche Anagho (Journal of Chemistry)
The production of methyl esters (biodiesel) by the transesterification of Podocarpus falcatus oil (PFO) with methanol was optimized by response surface methodology (RSM) using the Box-Behnken design. The effects of parameters such as temperature, reaction time, and alcohol/oil molar ratio using yield and viscosity as responses were investigated. The optimum conditions for the production of biodiesel were as follows: temperature at 65°C, reaction time of 180 min, and molar ratio of 10 : 1, while the minimum viscosity was obtained for a temperature of 50°C, a reaction time of 120 min, and a molar ratio of 10 : 1. Physicochemical characterization by infrared spectroscopy (FT-IR) and UV visible spectroscopy showed that the free fatty acid (FFA) content of Podocarpus oil was 1.9%, which is less than the maximum of 2% recommended for the application of the one-step alkaline transesterification process. Also, the biodiesel obtained from the oil was seen to consist mainly of methyl esters, and that its physicochemical characteristics are within the standard set by the American Standard for Testing and Materials (ASTM).